(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Aquatic environments are usually represented by physicochemical properties, including flow regime on riverbed configurations, sediment size and stability, and water quality. This monograph focuses on the habitat of submerged macrophytes. Recent changes to the aforementioned physicochemical properties because of human activities have altered the aquatic habitats for submerged macrophytes, resulting in increases in the number of invasive species and extinction of native species. The expansion of invasive species into new environments often changes the physicochemical properties of these environments through accumulation of fine materials or changes in water quality.